Civics Textbook Supplement Design Based on Pancasila Student Profiles to Increase Student Activity - Yanzi, Hermi; Mentari, Ana; Aransyah, Ade; Seftriyana, Elisa (UNDIKMA, 2024)
The condition of diverse learning needs and the rapid development of education requires textbooks prepared by the government to meet learning standards that are expected to fulfill the success of learning activities in schools. The results of the needs analysis of the Civics Junior High School Textbook in Bandar Lampung City show that there is a need for a complementary textbook that is expected to support typical Civics learning activities. This research method is a development research used to produce certain products, and test the effectiveness of these products. The development model and procedures used in this study are divided into 4 stages, 1) Needs Analysis Stage, 2) Product Design Stage, 3) Validation and Evaluation Stage, and Final Product Stage. The results of this study show that the use of textbook supplements has a significant impact on students' understanding and learning outcomes. Effectiveness testing shows that the average formative test results for students who use digital map learning are greater than the average formative test results for students who use conventional learning. Efficiency testing can be concluded that Civics learning, especially the material displaying a positive attitude towards the flow of drafting the foundation of the Indonesian state and norms in everyday life using textbook supplement learning has the efficiency of saving more time than learning that does not use textbook supplements. It can be concluded that students' attitudes towards the attractiveness of digital map learning that has been applied in experimental classes have a positive impact on learning outcomes.